Osteoma of mandibular condyle: a case report - Liaquat, Ahmad; Baig, Moghees Ahmad; Khan, Saqib Mehmood (Journal of Chitwan Medical College, 2020)
Condylar osteoma is a benign tumor involving the condyle of the mandible. It is a rare pathology of unknown etiology. It is thought that it may originate from either cartilage or embryonal periosteum. It is also possible that it may be a reactionary lesion triggered by trauma or infection. Here, we present a case report of a female patient aged 60 years with osteoma on the right condyle with trismus and facial deformity. We surgically removed the tumor using a pre-auricular approach.